PENGARUH PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN, KOMITMEN ORGANISASI, LOCUS OF CONTROL, DAN KOMPLEKSITAS TUGAS TERHADAP KESENJANGAN ANGGARAN (Studi Empiris pada SKPD Kabupaten Agam) - Eka Nopriyanti; Nur Azlina; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to invetigate the effect of budget participation, budget emphasis, organization commitment, locus of control, and task complecity on budgetary slack.While responden is consisted by the structural functionary in governmental institution of Agam Regency. The data was collected by distributing quetionnaires to 108 repondents, but only 78 respondents who fill out the questionnaires. The analysis tool used is multiple regression using SPSS program version 21. The results show that budget participation, budget emphasis, organization commitment, locus of control, and tas complecity have significant effect and poitive impact on budgetary slack. Based on the results.Keywords: Budget Participation, Budget Emphasis, Organization Commitment, Locus Of Control, and Task Complecity.